2014
DOI: 10.1111/jse.12112
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the cyclin gene family in plants

Abstract: Cyclins are key regulators of cell cycle progression. Previous studies have shown that cyclin genes in plants can be divided into 10 groups. However, because those studies only focused on genes from two well‐known model plants (i.e., Arabidopsis thaliana (L.) Heynh. and Oryza sativa L.), it remains unclear whether the 10 groups are reasonably defined. In this study, by analyzing the genomes of 10 representative plants (Chlamydomonas reinhardtii P. A. Dang, Physcomitrella patens (Hedw.) Bruch & Schimp., Selagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…We identified 658 CYCB genes in 24 angiosperms. Consistent with previous studies [6,23,24], the plant CYCB genes could be separated into three groups, with all species having the fewest members in Group 3. We observed that the expansion and shrinkage of CYCB members occurred in terms of copy-number within B. napus accessions and among angiosperm species, corresponding with previous studies [24][25][26].…”
Section: Characterization Of the Cycb Gene Familysupporting
confidence: 89%
“…We identified 658 CYCB genes in 24 angiosperms. Consistent with previous studies [6,23,24], the plant CYCB genes could be separated into three groups, with all species having the fewest members in Group 3. We observed that the expansion and shrinkage of CYCB members occurred in terms of copy-number within B. napus accessions and among angiosperm species, corresponding with previous studies [24][25][26].…”
Section: Characterization Of the Cycb Gene Familysupporting
confidence: 89%
“…Since the first plant cyclin gene was cloned in soybean [ 16 ], more cyclins have been found in various plants [ 11 , 12 ]. A previous study indicates that plant cyclins can be classified into 10 groups, but there are only eight ancestral genes in the most recent common ancestor (MRCA) of extant green plants [ 17 ]. Forty-nine cyclins have been identified in the Arabidopsis thaliana genome, which were assigned to A-, B-, C-, D-, H-, L-, T-, U-, SDS-, and J18-type.…”
Section: Introductionmentioning
confidence: 99%
“…Angiosperms have undergone an extensive expansion of the cyclin family in comparison to yeast and mammals, containing for instance a total of 10 different cyclin families with more than 50 protein‐encoding cyclin genes in Arabidopsis (Wang et al , 2004 ; Jia et al , 2014 ). For most of these genes, functional information is still lacking.…”
Section: Discussionmentioning
confidence: 99%